Physical activity and risk of pancreatic cancer in a central European multicenter case-control study - Brenner, Darren R; Wozniak, Magdalena B; Feyt, Clément; Holcatova, Ivana; Janout, Vladimir; Foretova, Lenka; Fabianova, Eleonora; Shonova, Olga; Martinek, Arnost; Ryska, Miroslav; Adamcakova, Zora; Flaska, Erik; et al. (Cancer causes & control, 2014)
PURPOSE: Findings from epidemiological studies examining physical activity in relation to pancreatic cancer risk have suggested decreased risks for physical activity; however, the results are inconsistent. METHODS: The association between occupational and leisure-time physical activity and risk of pancreatic cancer was examined among 826 pancreatic cancer cases and 930 age-, sex- and center-matched controls from a large multicenter central European study in Czech Republic and Slovakia recruited between 2004 and 2012. Data on physical activity including type and dose (frequency, intensity, and duration) were examined using multivariable-adjusted logistic regression models. RESULTS: Occupational physical activity was not significantly associated with risk of pancreatic cancer [odds ratio (OR) 0.90, 95 % confidence interval (CI) 0.71-1.15]. A 35 % decrease in risk of pancreatic cancer was observed for regular leisure-time physical activity (OR 0.65, 95 % CI 0.52-0.87). The risk estimates were significant for low and moderate intensity of activity with the strongest protective effect among individuals who exercised during more than 40 weeks per year. The results for cumulated leisure-time physical activity assessed 1 year prior to diagnosis achieved the same level of risk reduction. In addition, stronger risk estimates for leisure-time physical activity were observed among women (men: OR 0.74, 95 % CI 0.54-1.01; women: OR 0.53, 95 % CI 0.37-0.75). The findings for female participants were stronger for intensity and frequency of leisure-time physical activity, in particular for light and moderate activity (OR 0.43, 95 % CI 0.25-0.75; and OR 0.57, 95 % CI 0.37-0.88, respectively). CONCLUSION: These results provide evidence for a decreased risk of pancreatic cancer associated with regular leisure-time physical activity.
Keywords: Data Collection; Male; nádory slinivky břišní; lidé středního věku; zaměstnání; studie případů a kontrol; senioři nad 80 let; Motor Activity; Slovenská republika; Aged, 80 and over; sběr dat; Humans; Pancreatic Neoplasms; Middle Aged; senioři; rizikové faktory; Czech Republic; Česká republika; mužské pohlaví; Female; pohybová aktivita; Occupations; Aged; volnočasové aktivity; Case-Control Studies; Leisure Activities; ženské pohlaví; mladý dospělý; Adult; Young Adult; Slovakia; dospělí; lidé; Risk Factors